Precautions Meaning by Supplications of Al Sajad Book (Al Sahifa Al Sajadia) - Jamil Saadoun , Researcher. Ghufran; Ziara Qasim, Assist. Prof. Dr. Munther; Abbas Falih, Prof. Dr. Mortedha (Basra studies journal, 2023)
The sentence is based on many pillars, and each corner performs a specific function according to its different linguistic structures. Some of them are restricted to the meaning, and others are absolute common, so the research tries to stand at the limitations of the sentence such as the objects and others, aiming to reveal the semantics of precaution in the precepts in the supplications of Al- Sahifa al-Sajjadiya. The research also attempts to shed light on the semantic meaning in the light of its connection with the semantic clues such as the presumption of attribution and specification, revealing the impact of the context in determining the significance of the text.